The sinner. Season four [videorecording (DVD)] - Pullman, Bill; Fisher, Frances, 1952-; Kremelberg, Alice; Huff, Neal; Cheung, Cindy, 1970-; Wong, Ronin; Hecht, Jessica, 1965-; Mosley, Michael, 1978- (Universal Pictures Home Entertainment, 2022)
"Still reeling from the trauma of a previous case a year ago, the now-retired Harry Ambrose travels to Hanover Island in northern Maine for a recuperative getaway with his partner, Sonya. When an unexpected tragedy occurs involving the daughter of a prominent island family, Ambrose is recruited to help the investigation, only to be thrown into a mystery of mounting paranoia that will turn this sleepy tourist island, and Ambrose's life, upside down" --Container.